2017
DOI: 10.4314/ahs.v17i2.18
|View full text |Cite
|
Sign up to set email alerts
|

An under-diagnosed geriatric syndrome: sleep disorders among older adults

Abstract: Introduction: Sleep disorders are commonly under-diagnosed in the geriatric population. We aimed to determine the prevalence of sleep problems among older adults admitted to the geriatrics out-patient clinic. Methods: Two hundred and three patients (136 female) older than 75 years of age were included in the study. Patients underwent comprehensive geriatric assessment, including identification of sleep problems using the Sleep Disturbance Scale, Rapid eye movement (REM) sleep behavior disorder (RBD) Single-Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Some studies refer that sleep problems can be a risk factor to develop cognitive impairment, dependence on ADLs, and risk of falling. In the same way, older people, who have these alterations in their functioning and health status, usually have sleep problems like insomnia, parasomnia, or sleep apnea 2,12,13,[56][57][58] Specifically, our outcomes also reflected a significant relation between sleep parameters with these variables. Moreover, as Martins da Silva et al, 14 our analysis showed that the sleep quality and quantity positively contributed to daily activity and the performance of ADLs of participants.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Some studies refer that sleep problems can be a risk factor to develop cognitive impairment, dependence on ADLs, and risk of falling. In the same way, older people, who have these alterations in their functioning and health status, usually have sleep problems like insomnia, parasomnia, or sleep apnea 2,12,13,[56][57][58] Specifically, our outcomes also reflected a significant relation between sleep parameters with these variables. Moreover, as Martins da Silva et al, 14 our analysis showed that the sleep quality and quantity positively contributed to daily activity and the performance of ADLs of participants.…”
Section: Discussionmentioning
confidence: 69%
“… 1 As people age, the duration and quality of sleep are negatively influenced by alterations in its sleep-wake cycle, with less restful deep sleep and sleep stages fragmented by increased nocturnal awakenings. 2 , 3 Likewise, changes associated with the passage of time, such as changes in roles, environment, or healthy lifestyle habits, affect sleep status. 4 , 5 In the aging stage, sleep problems are often underdiagnosed, and their prevalence depends on social and environmental factors and daily habits and routines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structuring sleep hygiene and taking it into account in the examination and treatment process may contribute to alleviating insomnia in the elderly (14,16). However, studies have shown that sleep restriction and sleep hygiene, which are safe, effective, and inexpensive ways of treating insomnia in the elderly, are not used adequately to treat insomnia in older adults with depression (OADs) (14,18).…”
Section: Introductionmentioning
confidence: 99%
“…Restless leg syndrome (RLS) is the unpleasant feeling (numbness, ache, tingling) in the legs that cause urge to move, especially in the evening. It is also related with insomnia and sleep disruption and reported more prevalent in older adults (8,12). RLS is reported as a common cause of insomnia; as much as 85% of patients with RLS were reported to have insomnia (13).…”
Section: Introductionmentioning
confidence: 99%